Complicity of the intraneus and extraneus in the crimes of breach of duty: corruption of officials - Coronel Santa Cruz, Raul (2025)
It has been reaffirmed that complicity in acts of corruption is not limited exclusively to participation during the execution of the illicit act; in fact, complicity encompasses a broader spectrum of conducts that include the facilitation and subsequent concealment of the crime; this aspect is decisive in understanding how corruption operates. In fact, the intraneus, due to its internal position and its privileged access to resources and strategic decisions, plays a decisive role in the materialization of corruption. On the other hand, the participation of the extraneus, due to his external position, does not constitute a criminal structure of his own, since he acts outside the internal structure, does not have autonomy and does not have direct access or authority within the criminal act, since he has no control over resources or decision-making capacity within the institution; his participation as an accomplice or instigator is subordinated to the role of the public official.